Development of an analytical strategy for the determination of trace lead in hibiscus tea extract by double slotted quartz tube assisted flame atomic absorption spectrometry after manganese ferrite based dispersive solid phase extraction - Karaman, Devrim Nur; Serbest, Hakan; Bahcivan, Aleyna; Korkunc, Ummugulsum Polat; Bakirdere, Sezgin (ELSEVIER, 2023)
In this study, a manganese ferrite (MnFe2O4) based dispersive solid phase extraction method (MF-DSPE) was proposed for the determination of lead (Pb) ions in hibiscus tea by double slotted quartz tube flame atomic absorption spectrometry (SQT-FAAS). The MnFe2O4 nanoparticles used as sorbent were produced in high yields using a green and friendly microwave synthesis procedure. The limit of detection (LOD) was found to be 14.2 mu g/ L under the optimal conditions. Recovery experiments were performed to assess the applicability of the developed method using hibiscus tea as test sample matrix. High recovery results were obtained by applying the matrix matching calibration method. Thanks to the developed MF-DSPE-SQT-FAAS method, the detection sensitivity for lead was improved by about 108-folds according to the comparison of the slopes of the calibration plots of the FAAS and MF-DSPE-SQT-FAAS systems.
Keywords: Lead; Hibiscus tea; Dispersive solid phase extraction; Flame atomic absorption spectrophotometry; Microwave synthesis; ONLINE PRECONCENTRATION SYSTEM; WASTE-WATER; CADMIUM; BIOSORPTION; REMOVAL; COPPER; IONS; GENERATION; ADSORBENT; SAMPLES; Chemistry